Nonlinear analysis of reinforced concrete slab-on-girder bridges with and without intermediate diaphragms - Mohie E. Shoukry; Tarek I. Ebeido; Zaki I. Mahmoud; Heba S. Mohamed (Alexandria Engineering Journal)
This paper presents results obtained from a nonlinear finite element analysis of slab-on-girder reinforced concrete bridges. Nonlinearity included: concrete cracking, behavior of concrete in compression, and reinforcement yield. Twenty-seven bridges were analyzed under truck loads based on the Egyptian Code (ECP 201–2017) and the self-weight of the bridge structural elements. This study included three groups: Group 1 with variable spans (L = 15 m, 20 m, and 24 m) and widths (W = 7 m, 10.5 m, and 14 m) to investigate the effect of the aspect ratio. Group 2 bridges with variable spans and girder spacing (S = 2.1 m, 2.625 m, and 3.5 m), while keeping the width constant at W = 10.5 m. Group 3 is similar to Group 1 but introduces one intermediate diaphragm placed at the bridge mid-span, in addition to two diaphragms located at the supports. The finite element model was calibrated using field tests found in the literature. Based on the parametric study, it was found that the presence of intermediate diaphragms, significantly enhances the transverse load distribution, thus reducing the bending moment on the longitudinal girders. The degree of enhancement increases as the bridge width increases. The Egyptian Code lacks an equation for the moment distribution factor, so an empirical equation was proposed to predict the moment distribution factors for the interior girder of slab-on-girder bridges under ECP truck loads.